A study on the relationship of the theory of consumption values and flow on consumers behavioural to use online shopping in Malaysia - Ajay Kumar Marthai Veeran; Lim Jia Hui; Noor Shamira Mohd Shahabudin; Nurtehah Norman (2024)
This research is mainly focused on understanding the relationship between theory of consumption values and flow with online purchasing behaviour among consumers. Consumer behaviour is about the sensations, thoughts, feelings, and reactions that consumers have after purchasing the products or services through online shopping. At the same time, this paper was also carried out to investigate whether the value of usage and flow will influence online consumers’ behaviour. This is due to the fact that consumer’s behaviour is influenced by many different factors. This research focused on the consumers that have the previous experiences of online shopping. The scope of this research is among the youth or teenagers that always use online shopping platforms while purchasing products or services. This research will collect and analyse the data from 335 respondents that answered the questionnaire survey. This is to clearly understand the relationship between the consumers and online shopping behaviour when purchasing through online platforms. So, this study focuses on those elements that may influence the consumer’s behaviour when purchasing online, which include flow, economy, quality, and satisfaction.